2023
DOI: 10.3390/su15053982
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Effective Fall-Detection Framework for the Elderly Using Sensor-Based Technologies

Abstract: Falls are critical events among the elderly living alone in their rooms and can have intense consequences, such as the elderly person being left to lie for a long time after the fall. Elderly falling is one of the serious healthcare issues that have been investigated by researchers for over a decade, and several techniques and methods have been proposed to detect fall events. To overcome and mitigate elderly fall issues, such as being left to lie for a long time after a fall, this project presents a low-cost, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
1
2
0
Order By: Relevance
“…Interviews with staff to understand these incidents revealed that residents may not have been wearing their MGA when they fell. The research literature has found that wearing a fall detection device all the time can be frustrating or annoying, and the older person may also need to remember to wear the device (Hassan et al, 2023). This is consistent with what was found in this study.…”
Section: Decrease In "Unwitnessed Falls"supporting
confidence: 91%
“…Interviews with staff to understand these incidents revealed that residents may not have been wearing their MGA when they fell. The research literature has found that wearing a fall detection device all the time can be frustrating or annoying, and the older person may also need to remember to wear the device (Hassan et al, 2023). This is consistent with what was found in this study.…”
Section: Decrease In "Unwitnessed Falls"supporting
confidence: 91%
“…Additionally, other studies of both approaches sensor and vision-based indicated that using RF helps to enhance the results [34][35][36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, the specificity (precision) and sensitivity (recall) of the targeted class are calculated to assess the algorithm's predictive accuracy for that specific class. These metrics in ML are determined based on the rates of "TP-True Positive, TN-True Negative, FP-False Positive, and FN-False Negative" [89]. True positive and true negative predictions are divided by all positive and negative predictions, respectively.…”
Section: Evaluating Parametersmentioning
confidence: 99%